Resilience State Security and the Role Sedative Agents in Military Pharmacy for State Defense in Future War - Gilang Bhakti Nusantara; Syahrul Tuba (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
National defense is closely related to the role of an intelligence officer who is strong and capable of safeguarding the country's sovereignty. Intelligence covers many fields. One of those is medical intelligence. Mitragynine can be used as a sedative agent in a medical intelligence operation. To analyze a sedative agent in intelligent medical purposing of military aspect. This paper determines the role of Military Pharmacy in medical intelligence to support national defense using natural substances that contain a sedative agent. This research used narrative review method for this study obtained from Crossref, google scholar, PubMed, and Scopus range 2010 to 2021 in the English language, using the following terms: "National defense," "Medical intelligence," "Kratom" Mitragynine "Sedative agent" but we did not exclude out older works that were often cited and significant. Mitragynine binds to three types of receptors with varying affinities, with the highest affinity for μ, K, and δ-opioid receptors, which can be used as sedatives in medical intelligence to support national defense. Kratom is a plant endemic to Southeast Asia; this plant has a sedative effect at high doses. Kratom leaves contain thirty-seven alkaloid compounds. Both alkaloid compounds are Mitragynine and 7-hydroxymitragynine, both of which are included in the indole alkaloid compound, the main kratom compound. Plants that are used when facing the battlefield in maintaining national defense are very complex owned by the Indonesian state, that is the kratom plant which has a chance to strengthening people defense and security state facing of sixth generation war. This study needs to validate with more rigorous human clinical studies in the future.